UNDERSTANDING RESEARCH METHODS FOR SOCIAL EPIDEMIOLOGY: A NARRATIVE REVIEW: RESEARCH METHODS - Afrona Elisabeth Lelan Takaeb (STIKes Mandala Waluya Kendari, 2022)
Background: Students or health workforces who are interested in understanding social epidemiology are required to have an adequate competency of research. This paper aimed to describe about the difference between quantitative and qualitative methodological approach in social epidemiology and types epidemiological study. Methods: Method applied was a narrative review to 28 English Text books, 2 Grey Literatures and 3 supported articles as example. All of these literatures have been reviewed based on key concept according to the purpose of this paper. Results: The basic premise or paradigm underpinning quantitative and qualitative methodology is related to their ontology and epistemology. Quantitative research or ‘the science of number” is based on the ontology of “objectivism” and the epistemology of “positivist or realist or functional or naturalism or logical empiricism while Qualitative research or “the word science” is based on the ontology of “constructivism” and the epistemology of ‘interpretivism. Study in epidemiology is divided into two parts that are, observational studies and experimental studies. Types of observational studies are descriptive study and analytic such as cross sectional, case control study and cohort while its counterparts are randomized control trials (RCT), field trials, and community trials. Conclusion: Quantitative and Qualitative approach in research in social epidemiology is classified based on their ontology and epistemology. There are two studies in epidemiology, namely, observational study (descriptive and analysis) and experimental study.